CBCT analysis in osteoradionecrosis case followed by hyperbaric oxygen treatment (a case study) - Lusi Epsilawati (DiscoverSys Inc., 2016)
Osteoradinecrosis is an infectious disease and inflammation that occurs in the jaw after doing radio therapy. Radiographic picture of the disease is visible lesions lucent extensive radio in the jaw. In Clinical condition, seen fistula and abscess in the jaw. One therapy for the treatment of this condition is the Hyperbaric Oxygen. The purpose of this paper is to look casereport work hyperbaric oxygen therapy in treating osteoradionecrosis. Patient age55-year-old, woman, came with complaints of pain in Â left and right lower jaw, since one month ago, after doing radiotherapy for 6 months. Patients diagnosed osteoradionecrosis. for the healing, selected medical therapy and patients are advised for doing oxygen hyperbaric therapy in AL Minto Harjo hospital Jakarta. One month after doing hyperbaric oxygen therapies seen change and healing. Lesions that form still has the same broad but disappeared fistula, abscess dries, necrotic tissue disappeared / reduced as well as the formation of new bone matrix. As conclusion, , obviously able to heal lesions caused osteomielitys oxygen therapy hyperbaric osteoradionecrosis.